2014
DOI: 10.1063/1.4883243
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuational electrodynamics of hyperbolic metamaterials

Abstract: We give a detailed account of equilibrium and non-equilibrium fluctuational electrodynamics of hyperbolic metamaterials. We show the unifying aspects of two different approaches; one utilizes the second kind of fluctuation dissipation theorem and the other makes use of the scattering method. We analyze the near-field of hyperbolic media at finite temperatures and show that the lack of spatial coherence can be attributed to the multi-modal nature of super-Planckian thermal emission. We also adopt the analysis t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…4), while previous work [46] has shown that the expressions in Eqs. (21) are only compatible with βd sl 1. In both plots, we can see that for ω < γ the EMA description enters the sub-ohmic regime discussed above.…”
Section: Electromagnetic Scattering Near Nano-structuresmentioning
confidence: 97%
See 2 more Smart Citations
“…4), while previous work [46] has shown that the expressions in Eqs. (21) are only compatible with βd sl 1. In both plots, we can see that for ω < γ the EMA description enters the sub-ohmic regime discussed above.…”
Section: Electromagnetic Scattering Near Nano-structuresmentioning
confidence: 97%
“…where f = d A /d sl gives the filling factor of material A. Equations (21) correspond to the propagation of the electromagnetic field parallel ( ) or orthogonal ( ⊥ ) to the optical axis of the crystal, in our case the z-axis.…”
Section: Electromagnetic Scattering Near Nano-structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that HM can be used for near-field thermophotovoltaic applications [51,52], which HM have a large penetration depth of thermal radiation [53,54], which is an advantage also for the transport of near-field thermal radiation over far-field distances [55]. In addition, the possibility of having larger conduction by thermal radiation inside an HM than conduction by phonons and electrons has been discussed [56] as well as the thermodynamical potentials, the general laws of thermal radiation inside HM [57] and the coherence properties in the vicinity of HM [58]. Recently, also tunable hyperbolic thermal emitters have been introduced [59], and it was proposed to make the use of the hyperbolic 2D plasmons in graphene ribbons for elevated near-field heat fluxes [60].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the generality of the available theories, a closed-form expression for the heat transfer between three objects in vacuum has only recently been given [17], and has already provided several interesting applications to heat transfer amplification [33] and guiding [34]. Aside from the advances in general formalism, various applications have been investigated in recent nonequilibrium studies [35][36][37][38][39][40][41][42][43]. On the experimental side, the development of high-precision measurement devices has verified many theoretical predictions concerning radiative heat transfer [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%